Doing Business in Kenya 2010 - World Bank; International Finance Corporation (Washington, DC, 2013)
Doing Business in Kenya 2010 is a new sub-national report of the Doing business series on the sub-Saharan African region, following the sub-national doing business report on Nigeria. It measures business regulations and their enforcement in 11 Kenyan localities: Eldoret, Garissa, Isiolo, Kilifi, Kisumu, Malaba, Mombasa, Nairobi, Narok, Nyeri, and Thika. The localities can be compared against each other, and with 183 economies worldwide. Comparisons with other economies are based on the indicators in doing business 2010: reforming through difficult times, the seventh in a series of annual reports published by the World Bank and the International Finance Corporation. The indicators in doing business in Kenya 2010 are also comparable with the data in other sub-national doing business reports. The indicators are used to analyze economic outcomes and identify what reforms have worked, where, and why. Other areas important to business such as a country's proximity to large markets, the quality of infrastructure services (other than services related to trading across borders), the security of property from theft and looting, the transparency of government procurement, macroeconomic conditions, or the underlying strength of institutions are not directly studied by doing business.